A governança da água no comitê da bacia hidrográfica do rio Paranaíba - Castilho, Jefferson Henrique Morais (2019)
Water governance configures the establishment of processes and mechanisms by which different social groups articulate their objectives and decisions on how to manage water resources. This research aimed to analyze the contributions of the Paranaíba River Basin Committee (CBHRP) to water governance and to elucidate its weaknesses and potentialities. To this end, an investigation of the implementation process, trajectory and performance of the CBHRP and its implications for the multilevel water governance process was carried out, as well as to evaluate the water governance stage in the committee, based on the guiding principles of good governance of water resources. . From these tools it was possible to highlight the following potentialities: CBHRP is well structured, with plural, transparent participation and based on the legal provisions contained in PNRH, in addition to conducting self- assessment of its management. Among the weaknesses, we can mention: lack of integration between state and district policies, institutional fragmentation and lack of human and financial resources granted to contribute to the establishment of water resources policies; partial compliance with the principles of equity and inclusion and accountability. Given the above, it is concluded that the CBHRP, despite the weaknesses evidenced, is an effective space for mobilization and participatory practices with regard to water resources policies. It has good transparency and effective legal provisions that make up good governance of water resources.